ANALISIS PERILAKU EROSI PADA DASAR SUNGAI BAGIAN HILIR BANGUNAN GROUNDSILL - Pratikso, Pratikso; Rochim, Abdul; Fauzi, Mukh ”˜Allaam (Politeknik Negeri Semarang, 2024)
Local scour is the erosion of soil at the riverbed, often occurring due to changes inflow type that become concentrated, influenced by river morphology or the presenceof structures within the river. The hydraulic jump caused by flood discharge at thegroundsill structure of the Gung River leads to local scour downstream of thestructure. Insufficient mitigation of local scour downstream of the groundsill canresult in long-term damage to the structure itself. This study was conducted toanalyze the potential scour depth using empirical methods and modeling with HECRASsoftware. The analysis considers rainfall data over the past five years in theGung River Watershed (DAS) and soil particle diameters obtained from soilinvestigations in 2022. The analysis of scour depth, taking into account a 50-yearrainfall event and followed by flood discharge analysis for a 50-year return period(Q50), yielded a design discharge for analyzing local scour depth using the Laceymethod, with a depth of 7.95 m. Through modeling with HEC-RAS version 6.5, theresulting local scour depth was found to be 8.2 m.